Beer, couscous or porridge? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Biochemist Mamadou Dicko from the University of Ouagadougou, Burkina Faso, can tell from the polyphenol (antioxidant) and enzyme content in sorghum what it can best be used for. Studying 50 varieties, he found that high polyphenol levels and low...